РОЛЬОВА ПОЗИЦІЯ СУЧАСНОГО ВЧИТЕЛЯ (Педагогіка вищої та середньої школи, 2022)
The modern teacher's role position. In this article we discuss the professional training of teacher and focus your attention on an essential functions, which discharges the modern teacher. We accentuate teacher's position.